Susan Hobbs Gallery. (Toronto : Susan Hobbs Gallery, 1997)
Carr-Harris, Ian ; Celestino, Magdalen ; Collyer, Robin ; Fleming, Martha ; Lapointe, Lyne ; Groombridge, Brian ; Maggs, Arnaud ; Magor, Liz ; Meigs, Sandra ; Schelle, Susan ; Whiten, Colette ; Wiens, Robert ; Wiitasalo, Shirley
biografie
Published on the occasion of participation in The cutting Edge at ARCO '97
boek